Two Types of Philosophical Therapy: Wittgenstein’s Late Discovery of Freud - Thomas J. Spiegel (Nordic Wittgenstein Review, 2026)
A variety of influential readers of Wittgenstein endorse the view that Wittgenstein consistently held onto one conception philosophical therapy (the ‘singularity assumption’). This article argues against the singularity assumption such that there are two fundamentally different types of philosophical therapy present in the early and later Wittgenstein. This change is elicited by Wittgenstein ‘discovering’ the idea of psychoanalysis after the Tractatus, this discovery’s impact being more fundamentally than is usually assumed. To this end, the article offers a first comprehensive overview of direct and circumstantial historical evidence to pinpoint the earliest point of engagement of Wittgenstein with Freud’s work. The result is that, considering the relatively late ‘discovery’ of Freud, the dissolution of nonsense in the Tractatus can be qualified as a substantially different form of therapy, presenting a serious discontinuity in Wittgenstein’s metaphilosophical thought begotten by Wittgenstein’s introduction to Freud’s work in (most likely) 1919.